The Effect of Different Types of Black Spanish and Bourbon Red Turkey Eggs on Fertility, Hatching Power, Hatching Loss, and Hatching Weight - Nabawi, Ircham; Windyasmara, Ludfia (Jurnal Biologi Tropis, 2025)
This research aims to determine the effect of different types of turkey on fertility, hatchability, hatching loss and egg hatching weight. This research uses the Independent Sample T-Test. Treated with two types of turkey, Black Spanish and Bourbon Red. The parameters observed were fertility, hatchability, hatching loss, and egg hatching weight. The results of this study show that the average fertility of A= 80%, B= 80% shows no significant difference. The average hatchability of A= 58.3%, B= 33.3% shows significant differences. The average hatching loss of A = 36%, B = 32% shows significant differences. The average hatching weight of A=41.2g, B=49.7g shows significant differences. Based on the research results, it can be concluded that two types of turkey (Black Spanish) and (Bourbon Red) have a significant effect on hatchability, hatching loss and hatching weight. However, the two types of turkeys did not differ significantly in terms of egg fertility.